Haptic characterization of human skin in vivo in response to shower gels using a magnetic levitation device. Issue 1 (3rd June 2015) - Yardley, R.; Fan, A.; Masters, J.; Mascaro, S.
Abstract : Background/Purpose: Skin products such as shower gels have a direct impact on skin health and wellness. Although qualitative haptic characterization through explicit, verbal measures in consumer studies are often sufficient for general comparison on consumer perceived skin feel, a quantitative approach is desired to characterize minute changes in skin condition in response to various skin products. Prior research has sought to characterize the haptic properties of human skin in vitro and in vivo, but very few studies have compared the haptic effects of commercial skin products having relatively similar formulations. In addition, related studies have typically utilized simple, low‐precision devices and fixtures. The purpose of this study was to use a precision magnetic levitation haptic device to characterize the frictional properties of human skin in vivo before, during, and after treatment with commercially available shower gels, to capture the entire cycle of consumer experience on skin feel. Methods: A hybrid force‐position control algorithm was used to control a precision magnetic levitation haptic device with silicone tactor to stroke the human skin (on the volar forearm) in vivo . Position and force data were collected from 32 human subjects using eight different commercially available shower gels, while stroking the skin before, during, and after treatment. The data were analyzed to produce coefficients of friction and viscous damping constant, which were used as metrics for comparing the effects of each shower gel type. Other factors investigated include skin test location, order, and subject age and gender. Results: Results showed significant differences between the effects of eight various shower gels, especially after accounting for variance between subjects. Most notably, Shower Gel four with high level of petrolatum, along with Shower Gels five and six with low levels of castoryl maleate (a skin lipid analog), as well as Shower Gel two with high levels of vegetable oils yielded higher skin coefficients of friction 20 min after treatment, indicating higher levels of skin hydration than other shower gels without either high levels of skin beneficial agents or low levels of castoryl maleate. Conversely, Shower Gel eight treatment yielded the lowest skin coefficient of friction both immediately after rinsing and 20 min after treatment. In addition, when applied to the skin as un‐lathered gels, Shower Gels six and seven with acrylate polymers yielded viscous damping constants twice that of other gels, while Shower Gel three yielded the lowest. When lathered into foam on skin, Shower Gel eight yielded the highest viscous damping constant, while Shower Gel three, along with Shower Gels one and five yielded lower values than others. Conclusion: The results of this study show that different shower gels do have significant measurable differences in their effects on skin properties, and that using a high‐precision haptic device can be a useful tool for quantifying the haptic properties of skin in vivo .